Fiber Optic Ice Sensor for Measuring Ice Thickness, Type and the Freezing Fraction on Aircraft Wings - Aris Ikiades (Aerospace, 2022)
Ice accretion on an aircraft affects the aerodynamic performance of the wings by disrupting the airflow, increasing drag, and altering its flight characteristics, leading to a main or tail wing-stall and altimetry to aircraft loss. The current generation of ice-detection systems relies on environmental parameters to determine icing conditions, with the sensors usually located on the nose of the aircraft, giving no information on the ice accreted on the wings. This work focuses on modeling and developing a fiber-optic-array ice sensor, which illuminates and detects the reflected and scattered light directly from the ice surface and volume, and measures the accretion rate and type of ice on the wings. The ice morphology is influenced by the rate of freezing of the super-cooled droplets impacting the wings, and partially or totally trapping the dissolved gasses. This leads to the formation of rugged surfaces and ice shapes, which can be transparent or opaque, a process which is dependent on the local Freezing Fraction (FF) of the impinging super cooled water. The detection method relies on the optical characteristics of ice, affected by density and the size of micro-cracks and micro-bubbles formed during freezing. By using high Numerical Aperture (NA) fibers, it was possible to accurately measure the ice thickness, and to investigate a proof-of-concept experiment, correlating the optical diffusion to the FF of the ice on a wing.